Consumer Confidence Index in Coronavirus Disease (Covid-19) Era - Dunyati Ilmiah; Muhammad Galih Wonoseto (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2021)
The consumer confidence index is an economic indicator designed to measure consumer confidence or doubt about the economic conditions of a country. The consumer confidence index can have an impact on the level of consumer interest in shopping so that it affects business activities, industry, and has a direct impact on the rate of econom ic growth. The condition of the consumer confidence index continues to improve, even though it is still during the Covid-19 pandemic and is still in the pessimistic zone, namely the index is below 100, the August 2020 consumer confidence index is 86.9 that is higher than in July 2020 of 86.2. This study uses trend analysis to estimate or forecast the future, and data obtained from the Bank Indonesia Consumer Survey. The results of this study show that the improvement in consumer confidence is drive by consumer perceptions of current economic conditions, namely increased income, job availability, and purchasing of goods.